A vida nunca esteve tão insuportável: reflexões sobre o tédio contemporâneo e as músicas de rock da década de 80 - Oliveira, Adriana Aparecida Almeida de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Contemporaneity consists of the current time in which important changes and ongoing influences give the world new forms different from those canonized by the modernity due either to the intensification or radicalization of the modernization process or to the appearance of new process, among which those processes categorized as related to the postmodernity are also found. As per Harvey (1998), postmodernity is characterized by the association and acceptance of ephemeral things and temporary things, making the ideas of acceleration, instability, precariousness, metamorphosis, fragmentation futile, as well as other ideas that compose the human condition in the current time. In this scenario of loneliness, indifference and emptiness caused by velocity, distance from the other, and weakness of relationships, two forms of subjeticvation are highlighted: depression and boredom. The first one is largely found in the current times. However this research has pointed out boredom as a subjectivation typical of the contemporaneity due to its close relation with time, particularly as the expression of an attempt of time deceleration or protest against excessive things and a vertiginous lifestyle. Boredom is characterized by tiredness of living, depotentiation of life. The main purpose of this paper was to identify and analyze expressions of boredom in Brazilian culture, and its corpus consists of lyrics from Brazilian rock in the 80s that deal with boredom. Artistic and cultural productions are considered a safe way for capturing subjectivations emerging in a given time and space, since they act out as expression – symbolic manifestation – of human experience or the experienced reality. These cultural productions were addressed through content analysis, as per Bardin (2002). This method is quite proper for textual analysis, and it induces a systematic treatment of texts which allows the extraction of significat ...

A contemporaneidade constitui-se como sendo o tempo atual no qual mudanças importantes e outras ainda em curso estão dando feições ao mundo, diferentes daquelas consagradas pela modernidade, seja pela intensificação e radicalização do processo de modernização ou pela eclosão de novos processos, dentre eles, inclusive, aqueles que foram situados como próprios da pós-modernidade. Esta se caracteriza, segundo Harvey (1998), pela incorporação e aceitação do efêmero e do provisório, tornando mundanas as imagens de aceleração, instabilidade, precariedade, metamorfose, fragmentação e outras que compõem a condição humana na atualidade. Nesse cenário da solidão, da indiferença e do vazio produzido pela velocidade, pelo distanciamento do outro e pela brandura das vinculações e relacionamentos destacam-se duas formas de subjetivação: a depressão e o tédio. A primeira tem forte presença nos dias atuais, porém esta pesquisa destacou o tédio como a subjetivação típica do contemporâneo pela sua íntima ligação com o tempo, especialmente, como expressão de uma tentativa de desaceleração do tempo ou de protesto contra o excesso e um ritmo de vida vertiginoso. O tédio caracteriza-se pelo cansaço de viver, uma despotencialização da vida. O objetivo principal e central da presente pesquisa foi identificar e analisar as expressões do tédio na cultura, tomando como corpus letras de músicas, do repertório Rock Nacional, da década de 80, que versem sobre o tédio. As produções artístico-culturais são consideradas um caminho seguro para se captar as subjetivações emergentes num dado tempo e lugar, visto que elas funcionam como expressão - como manifestação simbólica - da experiência humana ou da realidade vivida. Estas produções culturais foram tratadas mediante uma Análise de Conteúdo, na linha proposta por Bardin (2002). Tal método é bastante apropriado para a ...
Keywords: Tedio; Cultura; Música; Boredom